Implementasi Permainan Edukatif Untuk Penguatan Literasi Keuangan Siswa Sekolah Dasar 34 OKU - Faisal Abror; Ade Irwana Suciati; Nabila Hadisti Putri; Reza Tri Anggraini; Lucyana Lucyana (Jurnal Dehasen Mengabdi, 2026)
Financial literacy at the elementary school level is a crucial foundation for developing responsible financial behavior in the future. However, students’ understanding of basic financial management concepts remains limited. This community service activity aims to enhance students’ financial literacy through the implementation of the Cash and Coin Challenge game as an interactive and contextual learning medium at SD Negeri 34 OKU. The program employed an educative and participatory approach through material delivery, game simulation, discussions, and simple evaluations. The results indicate that students gained a better understanding of basic financial concepts, including distinguishing needs from wants, setting spending priorities, and managing money responsibly. Game-based learning effectively increased students’ engagement and motivation. This activity contributes positively to strengthening early financial literacy and can serve as an alternative contextual learning model in elementary education. Sustainable implementation and integration into formal curricula are recommended to ensure long-term impact